Reprodutibilidade do teste de Atividade de Vida Di??ria (AVD) - Glittre em indiv??duos com doen??a de Parkinson - S??, Mariana dos Anjos Furtado de (2018)
Objective: Study I: Identify the evaluation instruments utilized to measure the Functional Capability (FC) and the performance in the activities of daily living (ADL) of people with Parkinson???s disease (PD) in clinical trials in the field of physiotherapy. Study II: Analyze the reproducibility of the ADL test ??? Glittre in individuals with Parkinson???s disease (PD) and analyze the minimum detectable change in this test results in subjects with PD. Methods and Materials: Study I: A systematic review was carried out with a search in four databases. Extracted terms from Descritores em Ci??ncias da Sa??de (DeCS) and Medical Subject Headings (MeSH) were utilized. The terms were Parkinson???s disease, Physiotherapy, Daily Activities, Functional Capability and randomized clinical trials, including the suggested synonyms, in the Portuguese, English and Spanish language. Clinical trials were included in which the outcome were Functional Capability (FC) and/or the Physical Activities of Daily Living (ADL) from subjects with PD submitted to Physical Therapy. Two independent evaluators selected studies based on the eligibility criteria of the PEDro scale. A third evaluator analyzed the differences between the evaluators that selected the studies. Study II: Population sample composed of 30 subjects with PD, mean age 62??9 years old, both sexes (17 men), 8 (26,6%) at the Stage 1 of the Hoehn and Yahr classification, 11 (36,7%) at Stage 2 and 11 (36,7%) at Stage 3. The Glittre test (GT), was made in the intra-rater analysis twice, by the same rater, with a 30-minute interval, and in the inter-rater analysis both tests were made, by two distinct raters, with an interval of 1 to 7 days. The Intraclass correlation coefficient (ICC) was used to the reproducibility analysis and the proposed test by Bland and Altman to agreement analysis. Results: Study I: 10 studies were found, all using the total UPDRS or their II and III domains to evaluate, respectively, the performance of physical activities of daily living and the motor performance. The Timed Up and Go (TUG), was utilized in two out of the ten selected studies, was the only utilized instrument to evaluate the proposed outcomes, already validated to PD, in addition to UPDRS. Several other general measures, such as the 6-minute walk Test (6WT) and the Activity Card Sort (ACS) were cited as tools developed to other clinical populations, with the objective of evaluate the FC and/or ADL. Study II: The results demonstrated that the Glittre test execution time was significantly shorter in the retest (Intra-rater) with ICC= 0,92 (95%, CI= 0,83-0,96; P<0,0001). The results of the second evaluator were significantly shorter ICC= 0,86 (95%, CI = 0,71-0,93; P<0,0001). The MDC was 0,24 minutes (Intra-raters) and 0,62 minutes (Inter-raters). Conclusion: The study I results suggest that validation studies of other instruments are necessary to be utilized, as alternatives, to the evaluation of these outcomes. In the study II, the presented differences among the evaluators demonstrate the best results at the second test, pointing that at least two repetitions are necessary to obtain reliable evaluations.